Waqf-Based Endowment Funds as a Sustainable Financing Model to Enhance University Education Quality in Indonesia - Ekawaty, Marlina; Rohman, Ghifary Duyufur; Alvira Aina (Global Review of Islamic Economics and Business, 2025)
Sustainable financing remains a significant challenge for higher education institutions in Indonesia as they strive to enhance educational quality and compete with leading global universities. One promising solution is the utilization of waqf-based endowment funds as a source of long-term financing. This paper aims to explore the financing and management models of waqf endowment funds to support the improvement of university education quality. The study examines the role of waqf endowment funds in creating a stable financial system and identifies the opportunities and challenges associated with implementing this model in Indonesia. To achieve these objectives, the research employs NVivo 12 qualitative data analysis software to systematically analyze relevant literature and data, allowing for the coding and categorization of themes related to waqf financing. The findings are expected to provide valuable insights for policymakers and universities regarding the governance of waqf endowment funds and how this model can be applied to advance infrastructure, research, and teaching in higher education institutions. Furthermore, this study highlights the importance of collaboration between the government, universities, and society to optimize waqf endowment funds as a sustainable economic resource that positively impacts the quality of national education in Indonesia.